SCIENTIFIC AND METHODICAL APPROACHES TO ADMINISTRATION OF INNOVATIVE AND TECHNOLOGICAL DEVELOPMENT OF PROCESSING ENTERPRISES IN THE CONTEXT OF EUROPEAN INTEGRATION - STADNYK, VALENTYNA; KASHTALJAN, OLEKSANDR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article highlights problematic aspects of functioning of processing industry enterprises of Ukraine in the context of European integration. The need for their technological renewal taking into account the requirements of the "green transition" of the world economy is emphasized. It is argued that this renewal should be based on a combination of resource and value approaches in the theory of economic growth and provide a technological basis for innovative activity of enterprises. A new term "innovative sensitivity of the production and technological systems of the enterprise" is introduced. The author's definition of this term, which is based on a proactive approach in management theory and forms the technological competitiveness of the enterprise in global markets, is formulated. It is emphasized that instrumentally such sensitivity is provided by technological capabilities of marketing-management, among which the leading place belongs to CRM technology. An algorithm for selecting new technology for the implementation of technological changes in industrial enterprises, adequate to the requirements of the "green transition", is developed. Logical components and iterations of the algorithm are based on the methodology of resource and value approaches to justification of management decisions and meet the principles of technological competitiveness of the enterprise in global markets. The algorithm identifies areas of formation of a set of criteria of assessment of the level of suitability of new technology for creation of innovation-sensitive production-technological system of an industrial enterprise. The selection algorithm includes an assessment of the overall investment needs for the process of technological renewal of the enterprise (including staff training) and the possibility of their minimization by choosing the optimal organizational form of technology transfer. The main macro-prerequisites for innovative and technological renewal of domestic processing enterprises are also highlighted.
Keywords: innovative and technological renewal; innovative sensitivity; production-technological system; marketing-management; algorithm of technological chain; technological competitiveness